Preventive Dental Care and Unmet Dental Needs Among Low-Income Children - Kenney, Genevieve M. (© American Journal of Public Health 2005, 2005)
Objectives. We examined the ways in which levels of preventive dental care and unmet dental needs varied among subgroups of low-income children. Methods. Data were drawn from the 2002 National Survey of America’s Families. We conducted bivariate and multivariate analyses, including logistic regression analyses, to assess relationships between socioeconomic, demographic, and health factors and receipt of preventive dental care and unmet dental needs. Results. More than half of low-income children without health insurance had no preventive dental care visits. Levels of unmet dental needs among low-income children who had private health insurance coverage but no dental benefits were similar to those among uninsured children. Children of parents whose mental health was rated as poor were twice as likely to have unmet dental needs as other children. Conclusions. Additional progress toward improving the dental health of low-income children depends on identifying and responding to factors limiting both the demand for and the supply of dental services. In particular, it appears that expanding access to dental benefits is key to improving the oral health of this population.